2021
DOI: 10.1002/rcm.9139
|View full text |Cite
|
Sign up to set email alerts
|

Rapid fingerprint analysis for herbal polysaccharides using direct analysis in real‐time ionization mass spectrometry

Abstract: Herbal polysaccharides have various potential medicinal values.Development of reliable analytical method for the fingerprint analysis of polysaccharides is critical for their quality assessment, origin identification, and authenticity evaluation.Methods: Mechanochemical extraction (MCE) was used to extract polysaccharide components from different herbal species. Intact polysaccharides were then directly analyzed by direct analysis in real-time mass spectrometry (DART-MS). Standard addition method with isotope-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Ambient MS in which analytes are ionized at ambient pressure is often employed ( Xin et al, 2014 ; Massaro et al, 2021 ; Pereira et al, 2021 ), although inductively coupled plasma (ICP) MS for multi-element fingerprinting ( Zhao et al, 2017 ) and matrix-assisted laser desorption/ionization (MALDI) MS ( Lai et al, 2012 ) have also been reported. Ambient ionization techniques applicable to herbal materials and products include desorption electrospray ionization (DESI) ( Talaty et al, 2005 ; Freitas et al, 2019 ), ESI on solid substrates ( Deng and Yang, 2013 ; Hu et al, 2014 ; Wang H. et al, 2014 ; Xin et al, 2014 ; Jun et al, 2016 ), tissue ESI and related techniques ( Chan et al, 2011 ; Liu et al, 2011 ; Hu et al, 2013 ), extractive ESI ( Lee et al, 2021 ; Zhang et al, 2022 ), direct analysis in real-time (DART) ( Kumar et al, 2015 ; Wang et al, 2021a ), and desorption atmospheric pressure chemical ionization (DAPCI) ( Pi et al, 2011 ).…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambient MS in which analytes are ionized at ambient pressure is often employed ( Xin et al, 2014 ; Massaro et al, 2021 ; Pereira et al, 2021 ), although inductively coupled plasma (ICP) MS for multi-element fingerprinting ( Zhao et al, 2017 ) and matrix-assisted laser desorption/ionization (MALDI) MS ( Lai et al, 2012 ) have also been reported. Ambient ionization techniques applicable to herbal materials and products include desorption electrospray ionization (DESI) ( Talaty et al, 2005 ; Freitas et al, 2019 ), ESI on solid substrates ( Deng and Yang, 2013 ; Hu et al, 2014 ; Wang H. et al, 2014 ; Xin et al, 2014 ; Jun et al, 2016 ), tissue ESI and related techniques ( Chan et al, 2011 ; Liu et al, 2011 ; Hu et al, 2013 ), extractive ESI ( Lee et al, 2021 ; Zhang et al, 2022 ), direct analysis in real-time (DART) ( Kumar et al, 2015 ; Wang et al, 2021a ), and desorption atmospheric pressure chemical ionization (DAPCI) ( Pi et al, 2011 ).…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
“…In DESI, the sample surface is exposed to an electrospray plume, while an ionizing noble gas stream (i.e., metastable He) is used in DART ( Gross, 2006 ). Using DART, botanical samples can be directly analyzed without any sample preparation ( Kumar et al, 2015 ; Wang et al, 2021a ). Ionizing gas is also used in DAPCI to desorb/ionize analytes from the plant samples ( Pi et al, 2011 ).…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
“…Whereas an important focus of AIMS in food and agriculture is from a safety and authentication perspective, ambient MS techniques also have their use in detecting potentially healthy and harmful natural products in food and plants, evaluating flavour compounds in food products, and studying the metabolomics of agricultural products and plants. PSI has been used to quantify flavonoids in citrus beverages 94 and analyse plants containing pharmacologically active ingredients, 95 whereas DART‐MS has been widely applied for the analysis of active ingredients in herbal supplements and plants 96–101 . These two techniques have also been utilized in the evaluation of sour compounds in tea and wine, 102 to measure artificial sweeteners in alcoholic beverages 103 and for the study of post‐harvest quality of vegetables 104 .…”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%
“…PSI has been used to quantify flavonoids in citrus beverages 94 and analyse plants containing pharmacologically active ingredients, 95 whereas DART‐MS has been widely applied for the analysis of active ingredients in herbal supplements and plants. 96 , 97 , 98 , 99 , 100 , 101 These two techniques have also been utilized in the evaluation of sour compounds in tea and wine, 102 to measure artificial sweeteners in alcoholic beverages 103 and for the study of post‐harvest quality of vegetables. 104 REIMS has also been applied to the study of omega‐7 phospholipids in marine consumer products.…”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%
“…Typically, biological techniques and chemical methods, such as mass spectrometry, gas chromatography, etc., can be used for adulteration detection [11][12][13]. However, these analyses require highly trained professionals, and also it is time-consuming.…”
Section: Introductionmentioning
confidence: 99%